The Current state of ride-sharing apps in Bangladesh: are they successful in achieving customer satisfaction? - Al Muhit, Abdullah (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.